Malthusian population dynamics: Theory and evidence - Quamrul Ashraf; Oded Galor (Brown University, Department of Economics, 2008)
This paper empirically tests the existence of Malthusian population dynamics in the pre-Industrial Revolution era. The theory suggests that, during the agricultural stage of development, resource surpluses beyond the maintenance of subsistence consumption were channeled primarily into population growth. In particular, societies naturally blessed by higher land productivity would have supported larger populations, given the level of socioeconomic development. Moreover, given land productivity, societies in more advanced stages of development, as reflected by their cumulative experience with the agricultural technological paradigm since the Neolithic Revolution, would have sustained higher population densities. Using exogenous cross-country variations in the natural productivity of land and in the timing of the Neolithic Revolution, the analysis demonstrates that, in accordance with the Malthusian theory, societies that were characterized by higher land productivity and an earlier onset of agriculture had a higher population density in the time period 1-1500 CE.
Keywords: N10; N30; N50; O10; O40; O50; 330; Growth; Technological Progress; Population Dynamics; Land Productivity; Neolithic Revolution; Malthusian Stagnation